Male involvement in promotion of safe motherhood in low- and middle-income countries: A scoping review. (December 2021) - Ladur, Alice Norah; van Teijlingen, Edwin; Hundley, Vanora
Abstract: Background: Maternal health programmes that focus on the woman alone are limiting in LMICs as pregnant women often relate to maternity services through a complex social web that reflects power struggles within the kinship and the community. Methods: A scoping review was conducted to explore the rationale for male involvement in maternal health in LMICs. This review was guided by the question: What is the current state of knowledge regarding the inclusion of men in maternal health services in LMICs? The literature search was conducted using mySearch, Bournemouth University`s iteration of the EBSCO Discovery Service (EDS) tool. The review process used the Preferred Reporting Items for Systematic Reviews to select papers for inclusion. Findings: Thirty three studies met the inclusion criteria. Findings describe the rationale for involving men in maternity care, alongside the criticisms and challenges inherent in engaging with men in maternal health. Involving men in maternity services can improve health outcomes for women and infants. Health strategies aimed at educating men are relevant in equipping men with knowledge and skills that help men to be supportive of women`s wellbeing during pregnancy and childbirth. Conclusion: Men can serve as advocates for women and reinforce their partner`s choices in accessing skilled care and infant feeding. Further research is required to examine the effect of male involvement on women`s autonomy and to assess health education interventions aimed at mitigating harmful outcomes of involving men in maternity services.